Who is Not Afraid of Richard Dawkins?: Using Google Trends to Assess the Reach of Influential Atheists across Canadian Secular Groups - Dilmaghani, Maryam (Studies in religion, 2020)
Google Trends data on search volumes of high profile atheist public figures are used to assess their relative reach among different types of seculars in Canada. The user query data mined from Google Trends are complemented with an extensive set of information extracted from the Canadian General Social Surveys of 2005 to 2016. The analysis shows that the reach of high profile atheists is positively correlated with the presence of strictly-seculars, a proxy for the atheists. The investigation produces no statistically significant correlation between the presence of other types of seculars, namely the unchurched believers and the nominal affiliates, and the search volumes for high profile atheists. This exploratory finding suggests that the influential atheists likely “preach to the choir,” catering to like-minded individuals, at the exclusion of those with relatively close but differing views on religion and spirituality.